Secondary radiation measurements for particle therapy applications: nuclear fragmentation produced by 4He ion beams in a PMMA target. (23rd January 2017) - Marafini, M; Paramatti, R; Pinci, D; Battistoni, G; Collamati, F; De Lucia, E; Faccini, R; Frallicciardi, P M; Mancini-Terracciano, C; Mattei, I; Muraro, S; Piersanti, L; et al.
Abstract: Nowadays there is a growing interest in particle therapy treatments exploiting light ion beams against tumors due to their enhanced relative biological effectiveness and high space selectivity. In particular promising results are obtained by the use of 4 He projectiles. Unlike the treatments performed using protons, the beam ions can undergo a fragmentation process when interacting with the atomic nuclei in the patient body. In this paper the results of measurements performed at the Heidelberg Ion-Beam Therapy center are reported. For the first time the absolute fluxes and the energy spectra of the fragments—protons, deuterons, and tritons—produced by 4 He ion beams of 102, 125 and 145 MeV u −1 energies on a poly-methyl methacrylate target were evaluated at different angles. The obtained results are particularly relevant in view of the necessary optimization and review of the treatment planning software being developed for clinical use of 4 He beams in clinical routine and the relative bench-marking of Monte Carlo algorithm predictions.